Evaluation of Escherichia coli concentrations in Crassostrea gigas and seawater in two oyster growing areas in the Gulf of Nicoya, Costa Rica - Vega-Corrales, Luis A.; Marín-Vindas, Carolina (Revista Ciencias Marinas y Costeras, 2014)
Costa Rica does not have references on the health quality of Crassostrea gigas growing areas, which can pose a potential public health risk. This study evaluated the temporal trends of Escherichia coli concentrations in the C. gigas oyster and in the seawater of Punta Cuchillo and Punta Morales growing areas as a basis for the classification and monitoring of bivalve mollusc production sites in the Gulf of Nicoya, Costa Rica. Monthly samples of seawater and C. gigas were collected from each site from July 2011 to June 2012, and their levels of E. coli were determined using the most probable number method. Temperature and salinity were recorded at a one meter depth. Precipitation data was provided by Instituto Meteorológico Nacional (the National Meteorological Institute). Results indicated that the evaluated areas are probably being affected by wastewater discharge. Punta Cuchillo and Punta Morales could be classified as class A or authorized areas for the production of bivalve molluscs. A significant seasonal variability of E. coli concentrations was determined in seawater and oysters from the Gulf of Nicoya, defined primarily by salinity. National legislation should be created to establish controls and implement a monitoring system ensuring the bacteriological quality of the areas used for the cultivation of bivalve molluscs in the country.